The Evolutionary Horizons of Social Systems - Ch, Ana Maria Serra; Vidal, Gerardo (Archives of Case Reports, 2025)
This document has been translated from Spanish into English using ChatGPT. While efforts have been made to ensure accuracy and maintain the original meaning, some nuances or interpretations may differ from the source text. For any clarification, please refer to the original document or contact the author. This brief article addresses the concern arising from the accelerated whirlwind of changes of all kinds experienced by our social systems, some of which have a significant evolutionary impact, largely driven by advances in science and technology. Particular interest has emerged in connecting certain properties inherent to the behavior of complex systems far from equilibrium—such as social systems—under the framework of properties currently studied in Complexity Sciences. The article outlines this concern, which is, for now, merely the beginning of what could develop into a groundbreaking investigation. It references laboratory simulation work aimed at understanding the evolutionary horizons of Chile’s social system. The text includes an example of some graphs that illustrate a potential method for detecting and anticipating possible evolutionary horizons of the social system, based on the role played by certain “attractor variables” within the system. However, the research is still exploratory, and this article serves merely as a general description of the initial concern.